The Application of Diorama Media to Enhance Student Interest in Learning the Animal Life Cycle Topic in Grade III SDN 011 Parit Aman, Rokan Hilir - Royannisa, Friska; Rahmi, Laili (The Future of Education Journal, 2025)
The use of learning media in the school is still relatively rare, especially in science subjects. As a result, the interest in learning among third-grade students is low. To address this issue, an action needs to be taken, one of which is the application of diorama media in the science learning process. This study aims to describe the implementation of diorama media to enhance student interest in learning the topic of animal life cycles in the third grade of SDN 011 Parit Aman, Rokan Hilir, and to examine the increase in student interest after the application of diorama media in the learning process. The research method used is Classroom Action Research (CAR). In this study, the subjects are third-grade students, totaling 20 students. The data collection techniques and instruments in this study include questionnaires and observation sheets. Based on the results of the classroom action research conducted over two cycles, it can be concluded that the application of diorama media in science learning on the topic of animal life cycles can enhance the interest in learning among third-grade students of SDN 011 Parit Aman, Bangko District, Rokan Hilir Regency. Additionally, learning with diorama media successfully achieved the predetermined success indicators, and students showed good learning interest.